The Vision of the World and the Openness of Meaning in Contemporary Seventies Poetry - Ali, Dr. Fardous Hassan Ali (Sulaimani Journal for Humanities, 2026)
The term "worldview" is one of the ideologies of modern criticism, targeting poetry as not limited to mere expression, but rather transcending it to reveal an unknown, invisible world that lies on the other side of poetry. This is where the poet's vision and his explorations truly translate, making it a tool for uncovering the secrets and silences of society, in an attempt to reform reality as part of his role within it. The research aims to read the poetic text with a constructive, obligatory reading, exploring its worldview and how poets employed it to endow their texts with technical connotations. It presents the experience of Iraqi poetry in the 1970s, based on a formative methodology, to examine poets' worldviews and how they embodied their texts in accordance with their aesthetic poetic visions. This results in what confirms that the future holds a broad reality encompassing the present and the future. It grants texts radiances that transcend the boundaries of direct expression, transcending meanings and symbols, and exploring beyond vocabulary, using an attractive language that gives it a philosophical dimension, launching it into the world.
Keywords: Worldview; openness of meaning; the 1970s generation